African Literary NGOs - Strauhs, Doreen. author. aut Link
XII, 243 p.
Keywords: Proposing the novel concept of the "literary NGO," this study combines interviews with contemporary East African writers with an analysis of their professional activities and the cultural funding sector to make an original contribution to African literary criticism and cultural studies.